2001
DOI: 10.1007/bf02345262
|View full text |Cite
|
Sign up to set email alerts
|

A method for detecting myocardial abnormality by using a total current-vector calculated from ST-segment deviation of a magnetocardiogram signal

Abstract: A simple method to determine the state of ischaemia or fibrosis of myocardial cells has been developed. This method uses the ST wave of 64-channel magnetocardiogram (MCG) signals to calculate three parameters from the current-arrow map of the normal component signal of the MCG. One parameter is a total current vector that is obtained through summation of all current arrows. Another is a variance current vector calculated from the differential vector of two total current vectors at different times. The third is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 42 publications
0
42
0
Order By: Relevance
“…This method has been used to visualise cardiac-muscle currents (HOSAKA and COHEN, 1976;NAKAYA et al, 1984). it simplifies the observation of pseudocurrent patterns in heart muscle as it does not require the solution of an inverse problem, and so we have also applied it to the analysis of human heart disease in adults and fetuses (KANDORI et al, 2001a;c, 2002).…”
Section: Fmcg Analysismentioning
confidence: 98%
“…This method has been used to visualise cardiac-muscle currents (HOSAKA and COHEN, 1976;NAKAYA et al, 1984). it simplifies the observation of pseudocurrent patterns in heart muscle as it does not require the solution of an inverse problem, and so we have also applied it to the analysis of human heart disease in adults and fetuses (KANDORI et al, 2001a;c, 2002).…”
Section: Fmcg Analysismentioning
confidence: 98%
“…To visualise the epileptic discharge current inside the brain two-dimensionally, we produced current-arrow maps by deriving the normal component Bz of the magnetic field (Kandori et al, 2001). Such current maps are useful for reviewing neural networks directly and topographically without dipole estimation, although the head sphere shape affects the current-arrow pattern.…”
Section: Signal Analysismentioning
confidence: 99%
“…Although a volume conductor and tissue anisotropy have an influence on the cardiac currents, this visualisation technique has provided a high detection rate in the diagnosis of ischaemic and arrhythmic heart diseases in adults (TSUKADA et al, 2000a;YAMADA, et al, 200 1;2002;KANDORI et al, 2001a;2002;SATO et al, 2001;2002;SHIONO et al, 2002;KANZAKI et al, 2003). In particular, spatial current dstributions estimated from MCGs taken from adults with long-QT syndrome (LQTS) have led to a more accurate characterisation of this syndrome and revealed that it actually consists of two sub-types .…”
Section: Introductionmentioning
confidence: 98%